(untitled) (Research, Society and Development, 2022)
The aim of this study was to determine whether a combination of seaweed flour (Lithothamnium calcareum) and a homeopathic added to broiler feed has a hepatoprotective effect capable of minimizing the negative impacts of aflatoxin B1 toxicosis. We used birds one day divided into four groups with six repetitions per group and 20 birds per repetition in a completely randomized design. The combination of seaweed flour + homeopathic product was identified as the test product (TP). The groups were identified as PC: intake of 300 µg/kg of AFB1 (positive control); PC+TP: intake of 300 µg/kg of AFB1 + 2 g/kg of TP; NC: birds that received control feed; and TP: supplemented with 2 g/kg TP. The birds in the PC+TP, NC and TP groups had the higher body weights on days 35 and 42 days than in the PC group. This same effect was also observed for daily weight gain and feed conversion for 1–42 days. A higher villus: crypt relationship was observed in PC + TP, NC and TP compared to PC. The seaweed flour combined with the TP minimizes the negative effects of AFB1 on the liver health of broilers and consequently avoids losses in zootechnical performance.